Ribosome associated protein(s) specifically bind(s) to the upstream activator sequence of the E. coli rrnA P1 promoter. - Nachaliel, N (1989)
A sequence located upstream to the E. coli rrnA P1 promoter is required for optimal promoter activity. Deletion of this sequence reduces in vivo transcription by 90%. Substitution of this upstream activating sequence with the unrelated bent DNA sequence of the kinetoplast of Crithidia fasciculata, restores in vivo expression to high levels. Cellular proteins which are present only in exponentially growing cells bind specifically to intact rrnA P1, but do not bind to the promoter missing the upstream activating sequence. These proteins are associated with the 30S ribosomal subunits but can be washed off with concentrated salt. The correlation between the binding activity and cell growth rate suggests a role for these proteins in the transcriptional control of rRNA synthesis.